Experience of Cryopreserved Fetal Thymus Application when Treating Puerperal Infections - Grischenko, V. I.; Avetisyan, N. N. (Problems of Cryobiology and Cryomedicine, 2006)
Investigation results testify to high efficacy of heterotopic transplantationÂ of cryopreserved human fetal thymus tissues, which increases an organismâ€™s immunological possibilities and is an active way for postoperative infections treatment.